2022
DOI: 10.1159/000527604
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Eating Attitudes and Risk for Developing Disordered Eating Behaviors in College Students with Subthreshold Eating Disorders: A Cohort Study

Abstract: <b><i>Introduction:</i></b> The number of young adults with eating disorders or subthreshold eating disorders has increased recently. Although disordered eating behaviors persist once they appear, there have been relatively few studies on factors that might cause disordered eating behaviors. The purpose of this study was to investigate how the eating attitudes of young adults change over time and the risk factors that increase disordered eating behaviors. <b><i>Methods:</… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…(35) Our study showed that non-medical college students have more chance of developing disordered eating attitudes. This result is backed by an abundance of literature that reports eating disorders are prevalent among college students (36)(37) (38). A study done in France showed that a quarter (24.8%) of the college student population likely had eating disorders (39).…”
Section: Discussionmentioning
confidence: 99%
“…(35) Our study showed that non-medical college students have more chance of developing disordered eating attitudes. This result is backed by an abundance of literature that reports eating disorders are prevalent among college students (36)(37) (38). A study done in France showed that a quarter (24.8%) of the college student population likely had eating disorders (39).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the persistence of depressive symptoms in late adolescence is predictive of subsequent mental health problems [31][32][33]. We previously reported that depressive symptoms were correlated with the severity of disordered eating behaviors in university students [34]. Therefore, we examined the effects of the pandemic on the mental conditions of firstyear university students in Japan, including depressive symptoms, eating behaviors, and stress-coping styles, and compared the current year's results with the previous year's results.…”
Section: Introductionmentioning
confidence: 89%
“…Entering university can be a moment in life marked by great social pressure, with situations and challenges that increase the levels of stress, anxiety, and depressive symptoms [ 12 ], contributing to an increased risk of dysregulation of eating and worsening of eating behaviors [ 13 ] and body image perception, leaving university students more vulnerable to eating disorders [ 14 ]. In this context, ME and IE are useful approaches to promote improvements in eating and mental health by helping students to focus on their own cues of hunger and satiety, rather than following fashion trends or giving in to social pressure [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%